Comparison of Two School-Based Oral Health Education Programs in 9-Year-Old Children. (April 2019) - Eden, Ece; Akyildiz, Melis; Sönmez, Işıl
This study evaluated the effectiveness of two school-based oral health education (OHE) programs on the oral health knowledge and behavior and oral hygiene of 9-year-old children in Turkey. The study included 1, 053 school children aged 9 years in Aydin, Turkey. This study was a prospective, two-arm, and parallel-group clinical trial between two different OHE programs. The dentist group received one lecture on OHE given by dentists in the classroom. The teacher group had a similar lecture given by school teachers, including supporting materials which were available throughout the academic year. Oral health knowledge and behavior were evaluated with a questionnaire at baseline, and then at 1 and 6 months. In total, 110 students were randomly selected to undergo a plaque accumulation assessment according to the Silness–Löe Index at baseline and 1 month later to determine the effects of the education programs on oral hygiene. At baseline, tooth-brushing frequency was similar in the study groups. Compared with baseline, the frequency of brushing increased significantly after 1 and 6 months in both groups ( p  < .001). Teacher education was more effective for teaching correct brushing techniques ( p  < .001). A significant decrease in plaque accumulation has been evaluated in both study groups at the 1-month examination after the education session ( p  < .05). Both OHE programs were found to generate improvements in knowledge and behavior of children on oral health and plaque control in the short term.